A preparation method of a dendrite fibrous zirconium-silicon oxide supported ruthenium catalyst with rich mesoporous structure and application of the catalyst in polyolefin hydrocracking into liquid fuel

CN122999181APending Publication Date: 2026-10-30GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610703680.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

此外,现有催化剂通常需要在较高的温度和压力下才能实现聚烯烃的完全裂解,且在反应过程中催化剂易因积炭等原因失活,循环使用性能不佳,进一步提高了运行成本

Benefits of technology

[0027]1、本专利以溶胶-凝胶法制备具备丰富介孔结构的树枝纤维状锆硅氧化物材料(ZrO2-SiO2)作为载体,将氯化钌、柠檬酸混合水溶液通过等体积浸渍法进行负载,经过干燥、研磨,再依次进行煅烧和还原制备Ru/ZrO2-SiO2催化剂,该催化剂催化性能稳定,选择性良好,催化反应条件温和,对环境友好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999181A_ABST
    Figure CN122999181A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with rich mesoporous structures, comprising synthesis of a dendritic fibrous zirconium silicon oxide carrier and synthesis of a Ru / ZrO2-SiO2 catalyst. The catalyst preparation method provided by the application is controllable in process, good in repeatability, stable in catalytic performance, good in selectivity, mild in catalytic reaction condition, and friendly to the environment; and after the catalyst is used for multiple cycles, the substrate conversion rate can still be maintained to be above 90% and the liquid hydrocarbon selectivity can still be maintained to be above 60%, good cycle use stability is exhibited, and the application prospect in the field of polyolefin waste resourceization for preparing high-value liquid fuels is broad.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a method for preparing a dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure and its application in the hydrogenation and cracking of polyolefins into liquid fuels. Background Technology

[0002] Polyolefins (PO) are a general term for thermoplastic resins polymerized from α-olefin monomers such as ethylene and propylene. Major types include high-density polyethylene (HDPE), low-density polyethylene (LDPE), and polypropylene (PP). These materials possess outstanding advantages such as low density, good chemical stability, excellent mechanical properties, and low processing costs, and are widely used in packaging, construction, automobiles, electronics, medical materials, and daily consumer goods. Over the past few decades, global demand for plastics has quadrupled. With the continuous surge in plastic production and consumption, plastic waste management has become a critical environmental issue. However, the carbon chain skeleton of polyolefins is mainly composed of inert C(sp...) 3 )−C(sp 3 Composed of π bonds, plastics are extremely difficult to degrade in the natural environment, and the accumulation of large amounts of waste plastics has caused serious "white pollution" and waste of resources.

[0003] Meanwhile, selective cleavage strategies targeting the C-C bonds of polyolefins include pyrolysis, hydrolysis, hydrocracking, and hydrogenolysis. Among these, the hydrocracking strategy using metal-acid bifunctional catalysts for polyolefins is the most noteworthy because it can cleave the C-C bonds of polyolefins under relatively mild conditions, producing high-value products such as fuels, waxes, and lubricants, representing a potential strategy for reducing dependence on fossil fuel resources.

[0004] Ruthenium-based catalysts have been widely used in the research of polyolefin hydrocracking due to their excellent catalytic performance in breaking C-C bonds. Conventional ruthenium-based catalysts tend to over-crack carbon chains during the reaction, leading to the generation of large amounts of low-value methane. This is partly due to the microporous structure of traditional molecular sieve supports severely limiting the accessibility of acidic sites, making it difficult for polyolefin macromolecules to diffuse and adsorb effectively; on the other hand, the diffusion restriction within the narrow pores also exacerbates the secondary cracking of cracking intermediates, further increasing methane selectivity. Furthermore, existing catalysts typically require high temperatures and pressures to achieve complete cracking of polyolefins, and are prone to deactivation due to coking and other factors during the reaction, resulting in poor recyclability and further increasing operating costs. Therefore, developing effective alternative strategies for the selective hydrocracking of polyolefins under mild conditions is of great significance. Summary of the Invention

[0005] To address the aforementioned shortcomings in existing technologies, the present invention aims to provide a method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure and its application in the hydrogenation and cracking of polyolefins into liquid fuels. The catalyst provided by the present invention exhibits stable catalytic performance, good selectivity, mild catalytic reaction conditions, and is environmentally friendly. Under mild conditions, it can convert polyolefins such as HDPE, LDPE, and PP into liquid fuels (mainly C5-C20 alkanes) with a high conversion rate (≥ 99%), and the selectivity of liquid products can be higher than 60%.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure, comprising the following steps:

[0007] (1) Synthesis of dendritic fibrous zirconium silicon oxide support:

[0008] (1.1) Measure 50~170 mL of tetraethyl orthosilicate and dissolve it in 300~1000 mL of p-xylene. Let it stand for 15~30 min to mix it evenly and obtain a transparent homogeneous solution A.

[0009] (1.2) Weigh 5.8~20.0 g of cetyltrimethylammonium bromide and 7.0~24.0 g of urea, dissolve them in water of the same volume as the p-xylene used in step (1.1), stir magnetically for 30 min at room temperature, add 9.0~35.0 g of ammonium zirconium carbonate, and continue stirring for 30 min to obtain a milky white homogeneous solution B;

[0010] (1.3) Under constant stirring, solution A is slowly added dropwise to solution B. After stirring for 30 min, 15-60 mL of n-pentanol is added dropwise and stirring is continued for 30 min to obtain mixed solution C.

[0011] (1.4) Heat the mixed solution C obtained in step (1.3) to 120~140℃ and reflux at a constant temperature for 5~8 h. Stop heating after reflux and add 100~500 mL of anhydrous ethanol. After the above mixed solution cools to room temperature, centrifuge and wash it. Then transfer the sample to an oven at a temperature of 50~100℃ and dry it for 8~24 h. After drying, grind it to obtain a white powder sample.

[0012] (1.5) The sample obtained in step (1.4) was calcined in an air atmosphere and then ground to obtain dendritic fibrous zirconium silicon oxide support ZrO2-SiO2.

[0013] (2) Synthesis of Ru / ZrO2-SiO2 catalyst:

[0014] (2.1) The prepared zirconium silicon oxide support ZrO2-SiO2 was placed in a vacuum oven for drying and dehydration treatment for 3-6 hours, and then cooled for later use;

[0015] (2.2) Prepare an impregnation solution with a ruthenium chloride concentration of 0.13 mol / L and a citric acid concentration of 0.2 mol / L;

[0016] (2.3) Place the dried zirconium silicon oxide carrier in an ultrasonic machine and gradually load the impregnation solution onto the surface of the zirconium silicon oxide carrier so that the zirconium silicon oxide carrier is just completely wetted. Then place it in a vacuum drying oven at a temperature of 60~100℃ for 4~6 h.

[0017] (2.4) After drying, cool to room temperature, take out the solid and grind it into powder in a grinding bowl. Then place it in a tube furnace for two calcination treatments to obtain Ru / ZrO2-SiO2 catalyst.

[0018] Furthermore, in step (1.4), the white precipitate is first recovered by direct centrifugation, then washed with ethanol and water and centrifuged three times each, and finally washed with ethanol and centrifuged to remove the remaining water in the sample.

[0019] Furthermore, the calcination conditions in step (1.5) are: heating to 550-600℃ at a heating rate of 3-5℃ / min and holding at that temperature for 5-8 h.

[0020] Furthermore, in step (2.4), the two calcination processes are carried out first in an air atmosphere and then in a hydrogen atmosphere.

[0021] Furthermore, the conditions for processing in an air atmosphere are: heating to 400-500℃ at a heating rate of 3-5℃ / min and holding at that temperature for 2-3 hours.

[0022] Furthermore, the conditions for processing under a hydrogen atmosphere are as follows: heating to 300-350℃ at a heating rate of 2-3℃ / min and holding at that temperature for 2-3 hours.

[0023] Application of a dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure: The application of the dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure prepared by the above method in the catalytic hydrocracking of polyolefins to prepare liquid fuel products.

[0024] Furthermore, the specific application is as follows: 50~200 mg Ru / ZrO2-SiO2 catalyst and 1.0~4.0 g high-density polyethylene are placed in a 50 mL sealed stainless steel mechanical reactor made of 316 L material, hydrogen gas of 1.0 MPa is introduced, and the reaction is carried out at a temperature of 250℃ for 100 min.

[0025] Furthermore, before the reaction, 3.0 MPa hydrogen gas needs to be introduced into the reactor three times to purge it.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. This patent uses dendritic fibrous zirconium silicon oxide material (ZrO2-SiO2) with rich mesoporous structure prepared by sol-gel method as a support, and loads ruthenium chloride and citric acid mixed aqueous solution by equal volume impregnation method. After drying, grinding, and then calcination and reduction in sequence, Ru / ZrO2-SiO2 catalyst is prepared. The catalyst has stable catalytic performance, good selectivity, mild catalytic reaction conditions, and is environmentally friendly.

[0028] 2. This invention provides a method that, without the need for any organic solvents and under mild conditions, can convert polyolefins such as HDPE, LDPE and PP into liquid fuels (mainly C5-C20 alkanes) with a high conversion rate (≥99%), and the selectivity of the liquid products can be higher than 60%.

[0029] 3. The catalyst preparation method provided by this invention is controllable and has good repeatability; and after multiple cycles, the catalyst can still maintain a substrate conversion rate of over 90% and a liquid hydrocarbon selectivity of over 60%, demonstrating good recycling stability and showing broad application prospects in the field of high-value liquid fuel production from polyolefin waste. Attached Figure Description

[0030] Figure 1 SEM images and mappings of ZrO2-SiO2 and Ru / ZrO2-SiO2 catalysts;

[0031] Figure 2 Powder X-ray diffraction patterns of ZrO2-SiO2 and Ru / ZrO2-SiO2 catalysts;

[0032] Figure 3 BET tests were performed on ZrO2-SiO2 and Ru / ZrO2-SiO2 catalysts. Detailed Implementation

[0033] The method of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure prepared by the present invention is abbreviated as Ru / ZrO2-SiO2 catalyst.

[0034] I. Preparation of a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure

[0035] Example 1

[0036] A method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure includes the following steps:

[0037] (1) Synthesis of dendritic fibrous zirconium silicon oxide support:

[0038] (1.1) Measure 85 mL of tetraethyl orthosilicate and dissolve it in 500 mL of p-xylene. Let it stand for 20 min to mix it evenly and obtain a transparent homogeneous solution A.

[0039] (1.2) Weigh 10.0 g cetyltrimethylammonium bromide and 12.0 g urea, dissolve them in 500 mL of water, and stir magnetically at 700 rpm for 30 min at room temperature. Then add 16.0 g ammonium zirconium carbonate and continue stirring for 30 min to obtain a milky white homogeneous solution B.

[0040] (1.3) Under constant stirring, solution A was slowly added dropwise to solution B. After stirring for 30 min, 30 mL of n-pentanol was added dropwise and stirring was continued for 30 min to obtain mixed solution C.

[0041] (1.4) Heat the mixed solution C obtained in step (1.3) to 130°C and reflux at a constant temperature for 6 h. After the reflux is completed, stop heating and add 300 mL of anhydrous ethanol. After the above mixed solution is cooled to room temperature, first centrifuge directly to recover the white precipitate. Then wash with ethanol and water and centrifuge three times each. Finally wash with ethanol and centrifuge to remove the remaining water in the sample. Then transfer the sample to an oven at 50°C to dry for 24 h. After drying, grind to obtain a white powder sample.

[0042] (1.5) The sample obtained in step (1.4) was placed in a tube furnace and calcined. It was heated to 550°C at a heating rate of 5°C / min in air atmosphere and held for 6 h. After calcination, it was ground to obtain dendritic fibrous zirconium silicon oxide support ZrO2-SiO2.

[0043] (2) Synthesis of Ru / ZrO2-SiO2 catalyst:

[0044] (2.1) The zirconium silicon oxide support was placed in a vacuum oven for drying and dehydration treatment for 3 h, and then cooled for later use;

[0045] (2.2) Prepare an impregnation solution with a ruthenium chloride concentration of 0.13 mol / L and a citric acid concentration of 0.2 mol / L;

[0046] (2.3) Place the dried zirconium silicon oxide support in an ultrasonic machine and use a pipette to gradually load the impregnation solution onto the surface of the zirconium silicon oxide support so that the zirconium silicon oxide support is just completely wetted. Then place it in a vacuum drying oven at 80°C for 6 hours.

[0047] (2.4) After drying, cool to room temperature, take out the solid and grind it into powder in a grinding bowl. Then place it in a tube furnace and heat it to 500°C at a heating rate of 5°C / min in air atmosphere and hold it for 2 hours. Then heat it to 300°C at a heating rate of 3°C / min in hydrogen atmosphere and hold it for 2 hours to obtain Ru / ZrO2-SiO2 catalyst.

[0048] Example 2

[0049] A method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure includes the following steps:

[0050] (1) Synthesis of dendritic fibrous zirconium silicon oxide support:

[0051] (1.1) Measure 50 mL of tetraethyl orthosilicate and dissolve it in 300 mL of p-xylene. Let it stand for 15 min to mix it evenly and obtain a transparent homogeneous solution A.

[0052] (1.2) Weigh 5.8 g of cetyltrimethylammonium bromide and 7.0 g of urea, dissolve them in 300 mL of water, and stir magnetically at 700 rpm for 30 min at room temperature. Then add 9.0 g of ammonium zirconium carbonate and continue stirring for 30 min to obtain a milky white homogeneous solution B.

[0053] (1.3) Under constant stirring, solution A was slowly added dropwise to solution B. After stirring for 30 min, 15 mL of n-pentanol was added dropwise and stirring was continued for 30 min to obtain mixed solution C.

[0054] (1.4) Heat the mixed solution C obtained in step (1.3) to 120°C and reflux at a constant temperature for 5 h. After the reflux is completed, stop heating and add 100 mL of anhydrous ethanol. After the above mixed solution is cooled to room temperature, first centrifuge directly to recover the white precipitate. Then wash with ethanol and water and centrifuge three times each. Finally wash with ethanol and centrifuge to remove the remaining water in the sample. Then transfer the sample to an oven at 80°C to dry for 16 h. After drying, grind to obtain a white powder sample.

[0055] (1.5) The sample obtained in step (1.4) was placed in a tube furnace and calcined. It was heated to 550°C at a heating rate of 3°C / min in air atmosphere and held for 4 h. After calcination, it was ground to obtain dendritic fibrous zirconium silicon oxide support ZrO2-SiO2.

[0056] (2) Synthesis of Ru / ZrO2-SiO2 catalyst:

[0057] (2.1) The zirconium silicon oxide support ZrO2-SiO2 was placed in a vacuum oven for drying and dehydration treatment for 5 h, and then cooled for later use;

[0058] (2.2) Prepare an impregnation solution with a ruthenium chloride concentration of 0.13 mol / L and a citric acid concentration of 0.2 mol / L;

[0059] (2.3) Place the dried zirconium silicon oxide support in an ultrasonic machine and use a pipette to gradually load the impregnation solution onto the surface of the zirconium silicon oxide support so that the zirconium silicon oxide support is just completely wetted. Then place it in a vacuum drying oven at 60°C for 6 hours to dry.

[0060] (2.4) After drying, cool to room temperature, take out the solid and grind it into powder in a grinding bowl. Then place it in a tube furnace and heat it to 400°C at a heating rate of 5°C / min in air atmosphere and hold it for 3h. Then heat it to 350°C at a heating rate of 3°C / min in hydrogen atmosphere and hold it for 2h to obtain Ru / ZrO2-SiO2 catalyst.

[0061] Example 3

[0062] A method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure includes the following steps:

[0063] (1) Synthesis of dendritic fibrous zirconium silicon oxide support:

[0064] (1.1) Measure 170 mL of tetraethyl orthosilicate and dissolve it in 1000 mL of p-xylene. Let it stand for 15 min to mix it evenly and obtain a transparent homogeneous solution A.

[0065] (1.2) Weigh 20.0 g cetyltrimethylammonium bromide and 24.0 g urea, dissolve them in 1000 mL of water, and stir magnetically at 700 rpm for 30 min at room temperature. Then add 35.0 g of ammonium zirconium carbonate and continue stirring for 30 min to obtain a milky white homogeneous solution B.

[0066] (1.3) Under constant stirring, solution A was slowly added dropwise to solution B. After stirring for 30 min, 60 mL of n-pentanol was added dropwise and stirring was continued for 30 min to obtain mixed solution C.

[0067] (1.4) Heat the mixed solution C obtained in step (1.3) to 140℃ and reflux at a constant temperature for 8 h. After the reflux is completed, stop heating and add 500 mL of anhydrous ethanol. After the above mixed solution is cooled to room temperature, first centrifuge directly to recover the white precipitate. Then wash with ethanol and water and centrifuge three times each. Finally wash with ethanol and centrifuge to remove the remaining water in the sample. Then transfer the sample to an oven at 80℃ to dry for 8 h. After drying, grind to obtain a white powder sample.

[0068] (1.5) The sample obtained in step (1.4) was placed in a tube furnace and calcined. It was heated to 550°C at a heating rate of 4°C / min in air atmosphere and held for 6 h. After calcination, it was ground to obtain dendritic fibrous zirconium silicon oxide support ZrO2-SiO2.

[0069] (2) Synthesis of Ru / ZrO2-SiO2 catalyst:

[0070] (2.1) The zirconium silicon oxide support was placed in a vacuum oven for drying and dehydration treatment for 4 h, and then cooled for later use;

[0071] (2.2) Prepare an impregnation solution with a ruthenium chloride concentration of 0.13 mol / L and a citric acid concentration of 0.2 mol / L;

[0072] (2.3) Place the dried zirconium silicon oxide support in an ultrasonic machine and use a pipette to gradually load the impregnation solution onto the surface of the zirconium silicon oxide support so that the zirconium silicon oxide support is just completely wetted. Then place it in a vacuum drying oven at 100°C for 4 hours to dry.

[0073] (2.4) After drying, cool to room temperature, take out the solid and grind it into powder in a grinding bowl. Then place it in a tube furnace and heat it to 450°C at a heating rate of 4°C / min in air atmosphere and hold it for 2.5 h. Then heat it to 325°C at a heating rate of 2.5°C / min in hydrogen atmosphere and hold it for 2.5 h to obtain Ru / ZrO2-SiO2 catalyst.

[0074] II. Performance Testing of the Ru / ZrO2-SiO2 Catalyst Prepared in This Invention

[0075] 2.1) SEM Testing

[0076] The microstructure and elemental distribution of ZrO2-SiO2 and Ru / ZrO2-SiO2 catalysts were characterized by SEM and EDS-mapping (see [link to SEM]). Figure 1 The ZrO2-SiO2 support exhibits a highly uniform spherical morphology with abundant dendritic fibrous mesoporous structures on its surface and a uniform particle size distribution, with an average size of approximately 317 nm. After Ru loading, the catalyst retains its microspherical morphology intact, without significant structural collapse or particle agglomeration, indicating good stability of the support framework. EDS quantitative analysis showed that the normalized mass fraction of Ru was 1.25 wt%, which is basically consistent with the theoretical loading. Simultaneously, elemental mapping confirmed that O, Si, and Zr elements were uniformly distributed within the microspheres, and Ru also exhibited a uniformly dispersed distribution without significant local enrichment, indicating that Ru species were highly dispersed on the support surface, providing sufficient active sites for the catalytic reaction. The synergistic effect of the abundant mesoporous structure and highly dispersed active sites of the catalyst can effectively promote the diffusion and mass transfer of polyolefin macromolecules, providing sufficient reaction space and active sites for the catalytic degradation process, demonstrating good potential for polyolefin catalytic conversion applications.

[0077] 2.2) XRD (Powder X-ray Diffraction) Test

[0078] Figure 2The XRD patterns of ZrO2-SiO2 and Ru / ZrO2-SiO2 are shown. The XRD pattern of the ZrO2-SiO2 support exhibits a broad peak at 23°, which is attributed to the characteristic signal of amorphous SiO2. No obvious crystalline phase diffraction peaks are observed in the full spectrum, indicating that the support has an overall amorphous structure. Compared to the unloaded ZrO2-SiO2, the XRD pattern of Ru / ZrO2-SiO2 shows six additional characteristic peaks at 38.4°, 43.3°, 44.0°, 58.3°, 69.4°, and 82.2°, corresponding to the (1 0 2), (0 0 2), (1 0 1), (1 0 2), (1 1 0), and (1 0 3) crystal planes of ruthenium (PDF #00-003-0663), confirming the presence of the Ru crystalline phase. The average crystallite size of Ru nanoparticles, calculated based on the Scherrer equation, is approximately 10.6 nm, indicating that Ru species exist as small crystallites on the support surface with good dispersion. The amorphous background peaks of the support did not change significantly due to Ru loading, suggesting that the introduction of Ru did not disrupt the support's framework structure. These highly dispersed Ru nanoparticles provide abundant active sites for the catalytic conversion of polyolefins, while the mesoporous structure of the support also provides channels for the diffusion of reactant molecules, which is beneficial for improving catalytic reaction efficiency.

[0079] 2.3) BET Test

[0080] The physical properties of the support and catalyst, such as specific surface area and pore structure, were analyzed using the N2 adsorption-desorption method. Figure 3 (a) Figure 3 The N2 adsorption-desorption curves in (c) show that both ZrO2-SiO2 and Ru / ZrO2-SiO2 exhibit type IV isotherms, and significant hysteresis loops appear in the range of relative pressure (P / P0) > 0.4, indicating that both materials have mesoporous structures. Specifically, ZrO2-SiO2 exhibits H2-type hysteresis loops while Ru / ZrO2-SiO2 exhibits H3-type hysteresis loops, indicating that the mesoporous structure of Ru / ZrO2-SiO2 prepared after ruthenium loading becomes more irregular compared to ZrO2-SiO2. Figure 3 (b) The Barrett-Joyner-Halenda (BJH) pore size distribution curves show that the ZrO2-SiO2 support exhibits a dual mesoporous structure, with a narrowly distributed small mesoporous peak at 2-3 nm and a strong main mesoporous peak at ~8 nm. After the introduction of Ru species, the intensities of both mesoporous peaks decreased significantly, especially the characteristic peak at ~8 nm, which almost disappeared, and the pore volume also decreased from 0.99 cm⁻¹. 3 / g decreased significantly to 0.58cm 3 / g. This result confirms that Ru nanoparticles are mainly confined within the mesoporous channels of the support, resulting in a decrease in the specific surface area and pore volume of the material, while still partially retaining the original hierarchical porous structure of the support.

[0081] Table 1. Pore structure analysis of the support and catalyst

[0082] <![CDATA[ZrO2-SiO2]]> 561.18 7.02 0.99 <![CDATA[Ru / ZrO2-SiO2]]> 465.63 5.00 0.58

[0083] III. Testing of the Ru / ZrO2-SiO2 catalyst prepared in this invention for the hydrocracking of polyolefins to produce liquid fuel products

[0084] 50 mg of Ru / ZrO2-SiO2 catalyst and 1.0 g of high-density polyethylene were weighed and placed into a 50 mL sealed stainless steel mechanical reactor (316 L). The reactor was purged three times with nitrogen gas at 3.0 MPa, then hydrogen gas at 1.0 MPa was introduced, and the reaction was carried out at 250 °C for 100 min. The catalytic reaction results are shown in Table 1.

[0085] Table 1 shows the results of the catalytic reaction.

[0086] <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 100 1 100 67.3 <![CDATA[SiO2]]> 1.0 g HDPE 250 100 1 0 0 <![CDATA[ZrO2-SiO2]]> 1.0 g HDPE 250 100 1 5.4 0 <![CDATA[Ru / SiO2]]> 1.0 g HDPE 250 100 1 75.4 5.7 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 200 1 100 61.4 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 300 1 100 50.9 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 50 1 54.7 45.3 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 275 100 1 100 29.8 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 225 100 1 82.1 63.5 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 200 100 1 46.5 60.5 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 100 2 100 65.4 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g HDPE 250 100 3 100 63.2 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g LDPE 250 100 1 100 67.6 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g PP 250 100 1 30.1 32.8 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g PP 250 200 1 65.3 51.3 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g PP 250 300 1 98.2 61.6 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g PP 250 600 1 100 47.7 <![CDATA[Ru / ZrO2-SiO2]]> 0.4 g HDPE, 0.3 g LDPE, 0.3 g PP 250 100 1 34.0 10.1 <![CDATA[Ru / ZrO2-SiO2]]> 0.4 g HDPE, 0.3 g LDPE, 0.3 g PP 250 200 1 57.3 31.3 <![CDATA[Ru / ZrO2-SiO2]]> 0.4 g HDPE, 0.3 g LDPE, 0.3 g PP 250 300 1 90.5 57.9 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g LDPE black mulch film 250 100 1 10.3 0 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g LDPE black mulch film 250 200 1 22.1 0 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g LDPE black mulch film 250 300 1 37.7 15.1 <![CDATA[Ru / ZrO2-SiO2]]> 1.0 g LDPE black mulch film 250 600 1 89.6 55.6

[0087] After the reaction was completed and the reactor was allowed to cool to room temperature, the gaseous products were collected using a Teflon gas sampling bag. The gaseous products were then analyzed using an Agilent GC7890B gas chromatograph equipped with an FID detector and an HP-PLOT-Q column. The solid-liquid mixture after the reaction was dissolved in cyclohexane and collected in centrifuge tubes. The catalyst and unreacted substrate were separated by centrifugation. The upper liquid phase was collected and filtered through a 0.22 μm organic membrane. One μL of the liquid sample was taken and qualitatively analyzed using a Shimadzu GCMS-QP2010NC (HP-5 capillary column, 30 m × 0.25 mm × 0.25 μm). Quantitative analysis was then performed using a Fuli GC9790 II gas chromatograph equipped with an FID hydrogen fire detector and an HP-5 column.

[0088] The catalytic hydrocracking reaction of HDPE revealed that the supported SiO2 and ZrO2-SiO2 do not possess the ability to depolymerize polyolefins. While the Ru / SiO2 catalyst, after ruthenium loading, exhibited hydrocracking capability for polyolefins, its liquid product selectivity was only 5.7%. However, the Ru / ZrO2-SiO2 catalyst with further zirconium incorporation demonstrated excellent performance. Through further optimization of reaction conditions, this catalyst achieved 100% conversion and a liquid hydrocarbon selectivity of 67.3% under conditions of 250℃, 1.0 MPa H2, and 100 min. Furthermore, under the same optimal reaction conditions, this catalyst also showed good activity for LDPE (100% conversion, 70.6% liquid selectivity). By extending the reaction time, this catalyst also demonstrated good conversion ability and liquid product yield for PP, various polyolefin plastic mixtures, and actual LDPE waste film, showcasing its application potential in the resource utilization of polyolefin waste.

[0089] IV. Performance and stability testing of the Ru / ZrO2-SiO2 catalyst prepared in this invention for the hydrocracking of polyolefins

[0090] 50 mg of Ru / ZrO2-SiO2 catalyst and 1.0 g of high-density polyethylene were weighed and placed into a 50 mL sealed stainless steel mechanical reactor (316 L). The reactor was purged three times with nitrogen gas at 3.0 MPa, followed by the introduction of hydrogen gas at 1.0 MPa. The reaction was carried out at 250 °C for 100 min. After the reaction, the catalyst was centrifuged and dried in an oven at 50 °C for 24 h. It was then directly placed back into the reactor with 1.0 g of high-density polyethylene for a cyclic test. The experimental results are shown in Table 2, where x in Ru / ZrO2-SiO2-Rx represents the xth cycle test.

[0091] Table 2 Results of the Cyclic Experiment

[0092] <![CDATA[Ru / ZrO2-SiO2-R1]]> 1.0 g HDPE 250 100 1 98.9 65.6 <![CDATA[Ru / ZrO2-SiO2-R2]]> 1.0 g HDPE 250 100 1 100 66.5 <![CDATA[Ru / ZrO2-SiO2-R3]]> 1.0 g HDPE 250 100 1 100 63.5 <![CDATA[Ru / ZrO2-SiO2-R4]]> 1.0 g HDPE 250 100 1 95.3 64.2 <![CDATA[Ru / ZrO2-SiO2-R5]]> 1.0 g HDPE 250 100 1 90.2 60.4

[0093] As shown in Table 2, the Ru / ZrO2-SiO2 catalyst exhibits excellent cycle stability in the HDPE hydrocracking reaction. Under the same conditions of 250℃, 1 MPa, and 100 min, after 5 cycles, the HDPE conversion remained above 90%, and the selectivity for liquid hydrocarbons remained stably above 60%, without significant deactivation. This indicates that the catalyst has good catalytic performance stability and possesses potential for practical application.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure, characterized in that, Includes the following steps: (1) Synthesis of dendritic fibrous zirconium silicon oxide support: (1.1) Measure 50~170 mL of tetraethyl orthosilicate and dissolve it in 300~1000 mL of p-xylene. Let it stand for 15~30 min to mix it evenly and obtain a transparent homogeneous solution A. (1.2) Weigh 5.8~20.0 g of cetyltrimethylammonium bromide and 7.0~24.0 g of urea, dissolve them in water of the same volume as the p-xylene used in step (1.1), stir magnetically for 30 min at room temperature, add 9.0~35.0 g of ammonium zirconium carbonate, and continue stirring for 30 min to obtain a milky white homogeneous solution B; (1.3) Under constant stirring, solution A is slowly added dropwise to solution B. After stirring for 30 min, 15-60 mL of n-pentanol is added dropwise and stirring is continued for 30 min to obtain mixed solution C. (1.4) Heat the mixed solution C obtained in step (1.3) to 120~140℃ and reflux at a constant temperature for 5~8 h. Stop heating after reflux and add 100~500 mL of anhydrous ethanol. After the above mixed solution cools to room temperature, centrifuge and wash it. Then transfer the sample to an oven at a temperature of 50~100℃ and dry it for 8~24 h. After drying, grind it to obtain a white powder sample. (1.5) The sample obtained in step (1.4) was calcined in an air atmosphere and then ground to obtain dendritic fibrous zirconium silicon oxide support ZrO2-SiO2. (2) Synthesis of Ru / ZrO2-SiO2 catalyst: (2.1) The prepared zirconium silicon oxide support ZrO2-SiO2 was placed in a vacuum oven for drying and dehydration treatment for 3-6 h, and then cooled for later use; (2.2) Prepare an impregnation solution with a ruthenium chloride concentration of 0.13 mol / L and a citric acid concentration of 0.2 mol / L; (2.3) Place the dried zirconium silicon oxide carrier in an ultrasonic machine and gradually load the impregnation solution onto the surface of the zirconium silicon oxide carrier so that the zirconium silicon oxide carrier is just completely wetted. Then place it in a vacuum drying oven at a temperature of 60~100℃ for 4~6 h. (2.4) After drying, cool to room temperature, take out the solid and grind it into powder in a grinding bowl. Then place it in a tube furnace for two calcination treatments to obtain Ru / ZrO2-SiO2 catalyst.

2. The method for preparing a dendritic fibrous zirconium silicon oxide-supported ruthenium catalyst with abundant mesoporous structure according to claim 1, characterized in that, In step (1.4), the white precipitate is first recovered by direct centrifugation, then washed with ethanol and water and centrifuged three times each, and finally washed with ethanol and centrifuged to remove the remaining water in the sample.

3. The method for preparing a dendritic fibrous zirconium silicon oxide-supported ruthenium catalyst with abundant mesoporous structure according to claim 1, characterized in that, The calcination conditions in step (1.5) are: heating to 550-600℃ at a heating rate of 3-5℃ / min and holding for 5-8 h.

4. The method for preparing a dendritic fibrous zirconium silicon oxide-supported ruthenium catalyst with abundant mesoporous structure according to claim 1, characterized in that, In step (2.4), the two calcination processes are carried out first in an air atmosphere and then in a hydrogen atmosphere.

5. The method for preparing the dendritic fibrous zirconium silicon oxide-supported ruthenium catalyst with abundant mesoporous structure according to claim 4, characterized in that, The conditions for treatment in air atmosphere are: heating to 400-500℃ at a heating rate of 3-5℃ / min and holding at that temperature for 2-3 hours.

6. The method for preparing a dendritic fibrous zirconium silicon oxide-supported ruthenium catalyst with abundant mesoporous structure according to claim 4, characterized in that, The conditions for processing under a hydrogen atmosphere are: heating to 300-350℃ at a heating rate of 2-3℃ / min and holding at that temperature for 2-3 h.

7. The application of a ruthenium catalyst supported on dendritic fibrous zirconium silicon oxide with abundant mesoporous structure, characterized in that, Application of the dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure prepared by any of the methods described in claims 1 to 6 in the catalytic hydrocracking of polyolefins to prepare liquid fuel products.

8. The application of the dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure according to claim 7, characterized in that, Weigh 50-200 mg of Ru / ZrO2-SiO2 catalyst and 1.0-4.0 g of high-density polyethylene and place them in a 50 mL sealed stainless steel mechanical reactor made of 316 L material. Introduce 1.0 MPa of hydrogen gas and react at 250 °C for 100 min.

9. The application of the dendritic fibrous zirconium silicon oxide supported ruthenium catalyst with abundant mesoporous structure according to claim 8, characterized in that, Before the reaction, hydrogen gas at 3.0 MPa needs to be introduced into the reactor three times to purge it.